Anomalous enhancement of valley polarization in multilayer WS2 at room temperature. Issue 16 (10th April 2017) - Su, Huimin; Wei, Chengrong; Deng, Aiying; Deng, Dongmei; Yang, Chunlei; Dai, Jun-Feng
Abstract : We probe the polarization of the "A" exciton photoluminescence from monolayer and multilayer WS2 at 10 K and 295 K under near-resonant and off-resonant conditions. Abstract : We probe the polarization of the "A" exciton photoluminescence from monolayer and multilayer WS2 at 10 K and 295 K under near-resonant and off-resonant conditions. The monolayer WS2 exhibits relatively low valley polarization, around 24% at 10 K and 8% at 295 K, while all multilayer WS2 samples show very high valley polarization, which is a more or less constant value of around 80% at 10 K under near-resonant excitation. At room temperature, it is observed experimentally that valley polarization in multilayer WS2 monotonously increases with shrinking of the indirect bandgap energy. The phonon-assisted intervalley scattering via the K–Γ–K(K′) valleys is identified as the primary valley polarization relaxation channel, which could be gradually suppressed as the thickness increases, leading to a valley polarization of up to 70% in multilayer WS2 (>3 unit layers).